Meat cold chain management in Mexican supermarkets - P. Arriaga-Lorenzo; E. Maldonado-Simán; R. Ramírez-Valverde; P. A. Martínez-Hernández; D. N. Tirado-González; L. A. Saavedra-Jiménez (Теория и практика переработки мяса)
The cold chain represents an important opportunity for the food industry to offer food safety and quality of perishable foodstuffs, mainly by maximizing shelf life through limiting bacterial growth. Especially meat products have a short shelf life due to their cold chain requirements. Refrigeration equipment must always be appropriately calibrated and monitored to provide the right temperature and ensure its correct performance. This study aimed to evaluate the cold chain at the retail link in supermarkets of the major commercial chains in Mexico during 2021 and 2022 by recording the surface temperature of pork, poultry, and beef cuts in open coolers. A general linear model was used for the statistical analysis in a completely randomized design. The study considered several factors, such as supermarket, season of the year, position inside the refrigerator, type of meat and environmental temperature. Cold chain breaks were detected in certain seasons of the year, in supermarkets, and even within the refrigerator; there were differences between positions where products were placed. The persistence of these variations in the cold chain represents a public health risk caused by the consumption of foods because a temperature increase can lead to a rise in the microbial load of meat products. Thus, meat cold chain requires integrated logistics management in order to maintain high quality of foods.